(untitled) (One Health & Risk Management, 2023)
Introduction. Interconnections between the religious and medical sectors are multifaceted and have existed for centuries, including partnerships that have evolved in recent decades, and integrating religion into health programs can provide some important outcomes for population health. Material and methods. A quantitative study was conducted among family doctors and representatives of the Orthodox church, between January and March 2022. A questionnaire was applied to 347 family doctors and 337 Orthodox priests. Results. Both doctors (60.1%) and priests (79.8%) consider the existence of barriers to cooperation between the two entities. Both doctors and priests see doctors as important actors in solving public health problems (98% and 96% respectively), the local public authority (82% and 53% respectively), while doctors consider the value of the church more important than priests do (45% compared to 31%). Measures that could improve the degree of collaboration between institutions, regular communication between actors is a priority in their view (78.1% doctors and 78% priests), while priests attest that collaboration initiatives from the central authority could increase the degree of collaboration (81.6%), collaboration initiatives from religious institutions could influence this process to a much lesser extent (29.7%). Conclusions. Both doctors and priests confirm the need to increase the degree of involvement in public health activities in the future.